Anesthetic inhibition of firefly luciferase, a protein model for general anesthesia, does not exhibit pressure reversal. - Moss, G W (1991)
The surprising observation that pressures of the order of 150 atmospheres can restore consciousness to an anesthetized animal has long been central to theories of the molecular mechanisms underlying general anesthesia. We have constructed a high-pressure gas chamber to test for "pressure reversal" of the best available protein model of general anesthetic target sites: the pure enzyme firefly luciferase, which accounts extremely well for animal potencies (over a 100,000-fold range). We found no significant pressure reversal for a variety of anesthetics of differing size and polarity. It thus appears that either firefly luciferase is not an adequate model for general anesthetic target sites or that pressure and anesthetics act at different molecular sites in the central nervous system.